Business Incubator Assistance as a Financial Literacy Mediator to Improve Financial Performance: A Study on SME of Business Incubator in Palu City, Indonesia - Zhahir, Rezki Amalia; Muslimin, M.; Zainuddin, Fatlina; Anisah, A. (Golden Ratio of Finance Management, 2025)
This study aims to analyze the role of Business Incubator assistance as a mediator between financial literacy and financial performance in SMEs assisted by the Palu City Business Incubator. Using a quantitative approach with path analysis techniques, data were obtained through a survey of fostered SMEs. The results showed that financial literacy has a positive and significant effect on financial performance but has no positive effect on mentoring, and mentoring also shows no significant effect on financial performance. These findings indicate that financial literacy directly contributes to improved financial performance without being mediated by mentoring. This study suggests that mentoring programs be designed more specifically to improve financial literacy so that the success of SMEs can be optimized through the synergy between strong financial literacy and relevant mentoring.